2010
DOI: 10.1371/journal.pone.0012388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on the Inhibition of C5 DNA Methyltransferases by Zebularine

Abstract: In mammals DNA methylation occurs at position 5 of cytosine in a CpG context and regulates gene expression. It plays an important role in diseases and inhibitors of DNA methyltransferases (DNMTs)—the enzymes responsible for DNA methylation—are used in clinics for cancer therapy. The most potent inhibitors are 5-azacytidine and 5-azadeoxycytidine. Zebularine (1-(β-D-ribofuranosyl)-2(1H)- pyrimidinone) is another cytidine analog described as a potent inhibitor that acts by forming a covalent complex with DNMT wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 56 publications
4
74
0
1
Order By: Relevance
“…Zebularine is a cytidine analog similar to decitabine and azacitidine that incorporates into DNA and forms a reversible complex with DNMTs, effectively preventing methylation (Zhou et al 2002;Champion et al 2010). RG108 is a small molecular inhibitor discovered through virtual screening that binds to the catalytic site of DNMT1 and shows reactivation of silenced tumor-suppressor genes such as P16, SFRP1, and TIMP3 (Brueckner et al 2005).…”
Section: Development Of Novel Dna Hypomethylating Drugsmentioning
confidence: 99%
“…Zebularine is a cytidine analog similar to decitabine and azacitidine that incorporates into DNA and forms a reversible complex with DNMTs, effectively preventing methylation (Zhou et al 2002;Champion et al 2010). RG108 is a small molecular inhibitor discovered through virtual screening that binds to the catalytic site of DNMT1 and shows reactivation of silenced tumor-suppressor genes such as P16, SFRP1, and TIMP3 (Brueckner et al 2005).…”
Section: Development Of Novel Dna Hypomethylating Drugsmentioning
confidence: 99%
“…In vitro experiments with synthetic oligonucleotides revealed that DNMTs covalently bind to zebularine-containing DNA molecules (Champion et al, 2010). Since we could not detect zebularine directly in DNA, we tested whether the NPAs could cause DNA damaging effects by reducing the amount of available DNMTs.…”
Section: Zebularine-triggered Dna Damage Response Is Independent Of Dmentioning
confidence: 99%
“…Both drugs are bound by DNA METHYLTRANSFERASEs (DNMTs) and form nucleoprotein adducts (NPAs), which effectively deplete the DNMT pool (Egger et al, 2004). In vitro studies using synthetic oligonucleotides containing 5-azacytidine or zebularine revealed higher stability of NPAs when compared with DNMT bound to 5-methyl-deoxycytosine (Champion et al, 2010;Kiianitsa and Maizels, 2013). The data generated using 5-azacytidine and 5-azadeoxicytidine suggest that NPAs represent a physical barrier for enzymes sliding along the DNA molecule and are repaired by HR coupled with replication restart and nucleotide excision repair (Kuo et al, 2007;Salem et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of ATM give rise to cell cycle defects in response to irradiation and radiosensitise cancer cells [35]. In this way, Zebularine and 5-aza-2'-deoxycytidine are employed as radiosensitizing agents [36,37]. Histone deacetylase inhibitors such as LBH589 and MS-275 have been shown to enhance radiosensitivity through the similar mechanisms [38].…”
Section: Dna Repair and Cancer Therapymentioning
confidence: 99%